The NLRP3–inflammasome as a sensor of organelle dysfunction - Seoane, Paula I.; Lee, Bali; Hoyle, Christopher; Yu, Shi; Lopez-Castejon, Gloria; Lowe, Martin; Brough, David (The Journal of cell biology, 2020)
Diverse pathogen- and damage-associated stresses drive inflammation via activation of the multimolecular NLRP3–inflammasome complex. How the effects of diverse stimuli are integrated by the cell to regulate NLRP3 has been the subject of intense research, and yet an accepted unifying hypothesis for the control of NLRP3 remains elusive. Here, we review the literature on the effects of NLRP3-activating stimuli on subcellular organelles and conclude that a shared feature of NLRP3-activating stresses is an organelle dysfunction. In particular, we propose that the endosome may be more important than previously recognized as a signal-integrating hub for NLRP3 activation in response to many stimuli and may also link to the dysfunction of other organelles. In addition, NLRP3–inflammasome-activating stimuli trigger diverse posttranslational modifications of NLRP3 that are important in controlling its activation. Future research should focus on how organelles respond to specific NLRP3-activating stimuli, and how this relates to posttranslational modifications, to delineate the organellar control of NLRP3.